(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electrical energy becomes necessary for human being. Generation of electrical energy mostly depends on fossils fuel, they are limited in nature and also responsible for environmental pollution. Renewable energy resources provides a better alternative for future. In comparison to conventional energy resources economical aspect is a major issue of renewable energy sources with the feasibility and efficiency. This paper investigates the performance analysis and control of Photovoltaic (PV)-wind hybrid system connected to electrical grid and feeds large plant with critical variable loads. The technique of extracting maximum power point is applied for the hybrid power system to capture maximum power under varying climatic conditions. Moreover, Control strategy for power flow is proposed to supply critical load demand of plant. The Dynamic performance of the proposed hybrid system is analyzed under different environmental conditions. The simulation results have proven the effectiveness of the proposed maximum power point tracking (MPPT) strategies in response to rapid variations of weather conditions during the day.